Hands-on data gathering - Mejía de la Pava, Claudia (Vestnik za tuje jezike, 2024)
Data collection is a fundamental aspect of linguistic and sociolinguistic research methodologies, and while many scholars may choose to gather their own data, others tend to rely solely on data that are readily available. There are various different methods of elicitation, including conducting interviews, questionnaires or leading focus groups to gather data, either as the main source of information or to complement existing material, which will most likely enhance both the quality of the research as well enriching the researcher’s personal experience. This paper aims to elucidate the experience gained by two researchers who implemented different data-collection methodologies during their research projects, to gather suitable data and conduct their analysis of the English language – one written the other oral – in two diverse, yet specialized, settings. They introduce their subjects of study and the communities in which the studies took place in order to help the reader get acquainted with the context, and then proceed to describe the processes they carried out. Their aim is to offer a retrospective on the decisions made, the evolution of their data-gathering approaches to determine the suitability of the focal methodologies, and the results. The aim of the paper is to contribute to the literature and applied linguistics research fields by disseminating empirical information on the collection of data within different communities of practice, so that it might be used, as a brief guide, to encourage and assist fellow researchers should they decide to embark in their own data collection projects.
Keywords: applied linguistics and sociolinguistics surveys; corpus linguistics; jezikoslovne raziskovalne metode; korpusno jezikoslovje; pridobivanje kvalitativnih podatkov; qualitative data gathering; raziskave s področja uporabnega jezikoslovja in sociolingvistike; research methods in linguistics; structured interviews and questionnaires; strukturirani intervjuji in vprašalniki